Stability and change in genetic and environmental influences on depressive symptoms in response to COVID-19 pandemic - Picardi, Angelo; Fagnani, Corrado; Gigantesco, Antonella; Toccaceli, Virgilia; Stazi, Maria Antonietta; Medda, Emanuela (Frontiers in Psychiatry, 2023)
Background The rapid spread of the new Coronavirus and the consequent restrictions to contain transmission generated an unprecedented psychological impact on the general population. The Italian Twin Registry performed a longitudinal study to investigate to what extent genetic and environmental influences contributed to changes in depressive symptoms. Methods Data from adult twins were collected. All participants completed an online questionnaire including the 2-item Patient Health Questionnaire (PHQ-2) just before (February 2020) and immediately after the Italian lockdown (June 2020). Genetic modeling based on Cholesky decomposition was used to estimate the role of genetic (A) and both shared (C) and unshared (E) environmental factors in the observed longitudinal course of depressive symptoms. Results Longitudinal genetic analysis was based on 348 twin pairs (215 monozygotic and 133 dizygotic pairs) with a mean age of 42.6 years (range 18–93 years). An AE Cholesky model provided heritability estimates for depressive symptoms of 0.24 and 0.35 before and after the lockdown period, respectively. Under the same model, the observed longitudinal trait correlation (0.44) was approximately equally contributed by genetic (46%) and unshared environmental (54%) influences, while longitudinal environmental correlation was lower than genetic correlation (0.34 and 0.71, respectively). Conclusions Although the heritability of depressive symptoms was rather stable across the targeted time window, different environmental as well as genetic factors seemed to act before and after the lockdown, which suggests possible gene-environment interaction.